High-resolution satellite remote sensing of provincial PM2.5 trends in China from 2001 to 2015. (May 2018) - Lin, C.Q.; Liu, G.; Lau, A.K.H.; Li, Y.; Li, C.C.; Fung, J.C.H.; Lao, X.Q.
Abstract: Given the vast territory of China, the long-term PM2.5 trends may substantially differ among the provinces. In this study, we aim to assess the provincial PM2.5 trends in China during the past few Five-Year Plan (FYP) periods. The lack of long-term PM2.5 measurements, however, makes such assessment difficult. Satellite remote sensing of PM2.5 concentration is an important step toward filling this data gap. In this study, a PM2.5 data set was built over China at a resolution of 1 km from 2001 to 2015 using satellite remote sensing. Analyses show that the national average of PM2.5 concentration increased by 0.04 μg·m −3 ·yr −1 during the 10th FYP period (2001–2005) and started to decline by −0.65 μg·m −3 ·yr −1 and −2.33 μg·m −3 ·yr −1 during the 11th (2006–2010) and the 12th (2011–2015) FYP period, respectively. In addition, substantial differences in the PM2.5 trends were observed among the provinces. Provinces in the Beijing-Tianjin-Hebei (BTH) region had the largest reduction of PM2.5 concentrations during the 10th and 12th FYP period. The greatest reduction rate of PM2.5 concentration during the 10th and 12th FYP period was observed in Beijing (−3.68 μg·m −3 ·yr −1 ) and Tianjin (−6.62 μg·m −3 ·yr −1 ), respectively. In contrast, PM2.5 concentrations remained steady for provinces in eastern and southeastern China (e.g., Shanghai) during the 12th FYP period. In overall, great efforts are still required to effectively reduce the PM2.5 concentrations in future. Highlights: A 1-km PM2.5 data set was built over China from 2001 to 2015. National PM2.5 increased from 2001 to 2005 and declined from 2006 to 2015. Great difference in the PM2.5 trend was observed among the provinces. The BTH region had more PM2.5 reduction during the 10th and 12th FYP period. Eastern and southeastern China had less PM2.5 reduction during the 12th FYP period.